Remote Versus In-Person Learning During COVID-19: Comparison of E-Cigarette Susceptibility and Ever Use Among a Diverse Cohort of 6th-Grade Students in Texas. Issue 2 (2nd April 2022) - Mantey, Dale S; Omega-Njemnobi, Onyinye; Ruiz, Felisa A; Chen, Baojiang; Springer, Andrew E; Kelder, Steven H
Abstract: Background: In response to SARS-CoV2 (COVID-19), school districts incorporated remote learning as a mitigation strategy. This study examines the association between classroom setting (ie, on-campus versus remote) and e-cigarette susceptibility or ever use among a sample of Texas public middle school students. Methods: Data from n = 985 students enrolled in the CATCH My Breath E-Cigarette Prevention Program trial were collected in Spring 2021. Participants were 6 th -grade students in urban Texas. E-cigarette use was examined using the "at-risk" definition described by FDA, indicating either: (1) susceptible never user; or (2) experimental ever use. A multilevel, logistic regression model examined the association between classroom setting and e-cigarette susceptibility/ever use. Covariates included sex, race/ethnicity, academic achievement, household e-cigarette use, perceived school connectedness, and school-level economic status. Models account for nesting within school district. Analyses stratified by race/ethnicity were also conducted. Results: Overall, 36.3% of the sample were susceptible never users or ever e-cigarette users. The sample was comprised of 55.0% on-campus and 45.0% remote learners. On-campus learners had greater odds of reporting e-cigarette susceptibility or ever use (aOR: 1.45; p = .014). These findings were observed among Latino (aOR: 1.77; p = .026) and White (aOR: 2.10; p = .099) but not African American/Black (aOR: 0.86; p = .728) youth. Conclusions: On-campus learning during the Spring 2021 semester was associated with greater risk for e-cigarette susceptibility or ever use among a diverse sample of 6 th -grade students. E-cigarette susceptibility and ever use is a risk factor for progression to long-term e-cigarette use in later adolescence. Implications: As school districts prepare to return to on-campus learning in 2022, a focused approach to e-cigarette prevention may be needed to prevent widespread e-cigarette initiation and continued use. Further, study findings demonstrate a need for further research on the school environment as a determinant of e-cigarette use.